Colour temperature tunable RGBW clusters with 3 control channels - Kalustova, Daria; Kornaga, Vasyl; Rybalochka, Andrii; Yu, Ying-Jie; Valyukh, Sergiy (Photonics Letters of Poland, 2020)
The work is devoted to development of a smart lighting system that is able to change correlated colour temperature and consists of tunable 4-components RGBW clusters controlled via three channels. It is shown that fixing a ratio between the intensities of white and red LEDs at a level of 100:9 enables obtaining high values of colour rendering in a wide range of correlated colour temperatures. A control of 3 from 4 channels simplifies the system. The influence of the red LED on CRI and luminous efficiency is analysed. Full Text: PDF References: J. Gooley, S. Rajaratnam, G. Brainard, R. Kronauer, C. Czeisler and S. Lockley, "Spectral Responses of the Human Circadian System Depend on the Irradiance and Duration of Exposure to Light", Sci Transl Med 2, 31 (2010) [CrossRef] A. Borisuit, F. Linhart, J. Scartexxini, M. Munch, Light Res Technol 47, 192 (2014) [CrossRef] Q. Dai, W. Cai, L. Hao, W Shi and Z. Wang, Light Res Technol 50 (8), 1198-1211 (2017), [CrossRef] V. Kornaga, V. Sorokin, A. Rybalochka, O. Oliinyk and N. Kornaga, Semicond Phys Quantum Electron Optoelectron 18, 302 (2015) [CrossRef] Illuminating Engineering Society, ANSI/IES TM-30-18 IES method for evaluating light source color rendition (2018). New York, NY[DirectLink] Commission International de l'Éclairage, CIE 224:2017 Colour fidelity index for accurate scientific use (2017). Vienna [CrossRef] V. Kornaga, D. Kalustova and O. Oliynyk, Int Sci Conf "Light and power eng: hist, probl, perspect" 6, 43 (2018) [DirectLink]